2014
DOI: 10.4329/wjr.v6.i5.203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different magnetic resonance imaging sequences for assessment of fistula-in-ano

Abstract: AIM:To assess agreement between different forms of T2 weighted imaging (T2WI), and post-contrast T1WI in the depiction of fistula tracts, inflammation, and internal openings with that of a reference test. METHODS:Thirty-nine consecutive prospective cases were enrolled. The following sequences were used for T2WI: 2D turbo-spin-echo (2D T2 TSE); 3D T2 TSE; short tau inversion recovery (STIR); 2D T2 TSE with fat saturation performed in all patients. T1WI were either a 3D T1-weighted prepared gradient echo sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
11
0
2
Order By: Relevance
“…20 reported that MRI had a high accuracy rate (94% and 93% respectively) in detecting primary tracts. Our study, as well as previous studies, support the concept that MRI is the imaging modality of choice in the preoperative assessment of anal fistulas 8,15,16 . In our study, MRI was found to misclassify 10% of primary tracts compared with the reference standard.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…20 reported that MRI had a high accuracy rate (94% and 93% respectively) in detecting primary tracts. Our study, as well as previous studies, support the concept that MRI is the imaging modality of choice in the preoperative assessment of anal fistulas 8,15,16 . In our study, MRI was found to misclassify 10% of primary tracts compared with the reference standard.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we used the diameter-based criteria, proposed by Torkzad et al . 16 , to classify fluid collections, i.e., a roundish fluid collection ≥ 10 mm was identified as an abscess while an elongated fluid collection < 10 mm was identified as a fistula (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative MRI can help in reducing the recurrence and is also helpful in the evaluation of complex fistulous disease process [15]. MRI sequences that are usually performed for perianal fistula assessment include plain and postcontrast T1-weighted and T2-weighted sequences [10]. STIR sequences have also been used [12].…”
Section: Discussionmentioning
confidence: 99%
“…MRI provides accurate details regarding anal canal anatomy and effectively delineates fistulous tracts along with other findings such as abscesses or secondary tracts [9]. In MRI pelvis, T1 weighted, T2 weighted, short tau inversion recovery (STIR) and T1 post-contrast with fat suppression sequences are commonly used to evaluate fistula-in-ano [10]. Recently, the role of diffusion-weighted imaging (DWI) has also been evaluated [11].…”
Section: Introductionmentioning
confidence: 99%